2010
DOI: 10.1007/s12011-010-8702-5
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Histomorphometry and Ultrastructure of Rats Treated with Cadmium and Ginkgo biloba

Abstract: The aim of this study is to investigate the association of a single low dose of Cd and daily doses of Ginkgo biloba extract (GbE) on the testis and accessory glands of rats. The animals were treated with a single dose of 3 µmol/kg body weight of cadmium chloride (CdCl₂) and/or 100 mg/kg body weight of GbE. The plasma testosterone levels; corporal, testicular, and accessory glands weight; gonadosomatic index, volumetric proportion; and absolute volume of testicular components did not change after the treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Blanco et al. () reported a similar result of Leydig cell nuclear shrinkage, while de Souza Predes, Monteiro, Matta, Garcia, and Dolder () observed fewer mitochondria with dense cytoplasmic matrix. Furthermore, steroidogenesis has been reported to take place within the Leydig cells of the testis, and the production of testosterone is influenced by the activity of LH on the Leydig cells.…”
Section: Discussionmentioning
confidence: 84%
“…Blanco et al. () reported a similar result of Leydig cell nuclear shrinkage, while de Souza Predes, Monteiro, Matta, Garcia, and Dolder () observed fewer mitochondria with dense cytoplasmic matrix. Furthermore, steroidogenesis has been reported to take place within the Leydig cells of the testis, and the production of testosterone is influenced by the activity of LH on the Leydig cells.…”
Section: Discussionmentioning
confidence: 84%
“…In the current work, numerous intercellular areas were noticed in-between the germinal cells lining the seminiferous tubules. This is attributed to loosening of cell-cell connections and these gaps caused shrinkage of both germ and Sertoli cells [14]. A previous study observed disarrangement of germ cell structure and function that is due to elevated level of ROS in the membrane lipids [16,56].…”
Section: Discussionmentioning
confidence: 94%
“…Fifty‐six‐day treatment of animals with oral administration of GB extract (a commercial product containing 19.2 mg/ml ginkgo flavonoids and 4.8 mg/ml terpenelactone) with the dose of 100 mg/kg prevented the cellular histomorphological alterations. The authors declared that the relation of these protective effects of GB to its antioxidant properties needs to be confirmed with more investigations (de Souza Predes, Monteiro, Matta, Garcia, & Dolder, ).…”
Section: Chemical Toxicitiesmentioning
confidence: 99%
“…, the single dose injection of 3 μmol/kg cadmium chloride, after 56 days, resulted in decreased volume of rat leydig cells, their cytoplasm, and nucleus; however, it did not induce any significant changes in the blood testosterone level, the size of each testicular parenchyma component, and the number of leydig cells. Fifty-six-day treatment of animals with oral administration of GB extract (a commercial product containing 19.2 mg/ml ginkgo flavonoids and 4.8 mg/ml terpenelactone) with the dose of 100 mg/kg prevented the cellular histomorphological alterations.The authors declared that the relation of these protective effects of GB to its antioxidant properties needs to be confirmed with more investigations(de Souza Predes, Monteiro, Matta, Garcia, & Dolder, 2011).…”
mentioning
confidence: 99%